PROPYLENE GLYCOL INTAKE FROM MEDICATIONS USED ON PAEDIATRIC INTENSIVE CARE. Issue 8 (11th July 2014) - Patel, C; Langley, C; Isaac, R
Abstract : There is an increasing number of reports of propylene glycol (PG) toxicity in the literature, regardless of its inclusion on the Generally Recognized as Safe List (GRAS).1 PG is an excipient used in many medications as a solvent for water-insoluble drugs. Polypharmacy may increase PG exposure in vulnerable PICU patients who may accumulate PG due to compromised liver and renal function. The study aim was to quantify PG intake in PICU patients and attitudes of clinicians towards PG. Method A snapshot of 50 PICU patients oral or intravenous medication intake was collected. Other data collected included age, weight, diagnosis, lactate levels and renal function. Manufacturers were contacted for PG content and then converted to mg/kg. Excipients in formulations that compete with the PG metabolism pathway were recorded. The Intensivists' opinions on PG intake was sought via e-survey. Results The 50 patients were prescribed 62 drugs and 83 formulations, 43/83 (52%) were parenteral formulations. Median weight of the patients was 5.5 kg (range 2–50 kg), ages ranged from 1 day to 13 years of age. Eleven of the patients were classed as renally impaired (defined as 1.5 times the baseline creatinine). Sixteen formulations contained PG, 2/16 were parenteral, 6/16 unlicensed preparations. Thirty-eight patients received at least one prescription containing PG and 29/38 of these patients were receiving formulations that contained excipients that may have competed with the metabolic pathways of PG. PG intake ranged from 0.002 mg/kg/day to 250 mg/kg/day. Total intake was inconclusive for 2 patients due to a of lack of availability of information from the manufacturer; these formulations were licensed but used in for off-label indications. Five commonly used formulations contributed to higher intakes of PG, namely co-trimoxazole, dexamethasone, potassium chloride, dipyridamole and phenobarbitone. Lactate levels were difficult to interpret due to the underlying conditions of the patients. One of the sixteen intensivist was aware of PG content in drugs, 16/16 would actively change therapy if intake was above European Medicines Agency recommendations. Conclusions Certain formulations used on PICU can considerably increase PG exposure to patients. Due to a lack of awareness of PG content, these should be highlighted to the clinician to assist with making informed decisions regarding risks versus benefits in continuing that drug, route of administration or formulation.